Chemosensory Receptors in the Larval Maxilla of Papilio hospiton - Crava, Cristina M.; Bobkov, Yuriy V.; Sollai, Giorgia; Anfora, Gianfranco; Crnjar, Roberto; Cattaneo, Alberto Maria (Frontiers in Ecology and Evolution, 2022)
Among the butterflies of the genus Papilio (Lepidoptera: Papilionidae), Papilio hospiton (Géné) has a geographical distribution limited to the Mediterranean islands of Sardinia (Italy) and Corsica (France). This is mainly due to the host-range that includes only a few plant species of Apiaceae and Rutaceae growing on these islands. In a previous electrophysiological investigation conducted on the maxillary gustatory system of larvae of P. hospiton and its closely phylogenetically related species P. machaon, a significantly higher spike activity was shown for the gustatory neurons of lateral and medial styloconic sensilla in P. hospiton when bitter compounds were tested. This effect was possibly correlated to the limited host choice range for P. hospiton. To shed light on the molecular aspects of this phenomenon, we investigated the expression pattern of sensory-related sequences by conducting a transcriptomic analysis from total RNA isolates of P. hospiton larval maxillae. We identified several transcripts that may be involved in taste (one gustatory receptor, one divergent ionotropic receptor and several transient receptor potential channels, TRPs) as well as transcripts supporting an olfactory function for this appendage, including odorant receptors (ORs), antennal ionotropic receptors (A-IRs), sensory membrane neuron proteins (SNMPs) and odorant-binding proteins (OBPs). We used Human Embryonic Kidney (HEK293A) cells to heterologously express two of the identified receptors, PhospOR1 and PhospPain, together with their orthologues from P. machaon, for functional characterization. While our data suggests no activation of these two receptors by the ligands known so far to activate electrophysiological response in larval maxillary neurons of Papilio species, nor temperature activation of both Papilio TRPA-channel Painless, they represent the first attempt in connecting neuronal activity with their molecular bases to unravel diet specialization between closely related species.